2011
DOI: 10.17925/usn.2011.07.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Therapeutic Options for Gait and Balance in Parkinson’s Disease

Abstract: There is a need to explore non-dopaminergic approaches to treating balance and gait problems in PD. There is emerging evidence on the role of cholinergic denervation of the PPN-thalamus system and falls in PD. Preliminary clinical trial data suggest that the subgroup of PD patients with frequent falls may be suitable candidates for future cholinergic augmentation clinical trials. Recent controlled clinical trials using methylphenidate have been unable to confirm earlier reports of improved gait in PD. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 136 publications
0
11
0
Order By: Relevance
“…Most studies [42][43][44] reported that handgrip strength, which is generally used as a substitute measure of overall individual muscular functioning, is consistently associated with mortality even adjusting for potentially confounding variables. The FTSS test, which examines the ability to transfer from a sitting to a standing position [45] and is strongly related to several physiological sensory and motor subsystems that contribute to balance adjustment and dynamic postural control, may help to identify those at risk of adverse health, including dementia [46,47]. Cesari et al [44] found that the FTSS test, as a subtest of the Short Physical Performance Battery, was able to strongly predict mortality (hazard ratio, 0.54; P < 0.01) in a similar way to the complete Short Physical Performance Battery score (hazard ratio, 0.64; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies [42][43][44] reported that handgrip strength, which is generally used as a substitute measure of overall individual muscular functioning, is consistently associated with mortality even adjusting for potentially confounding variables. The FTSS test, which examines the ability to transfer from a sitting to a standing position [45] and is strongly related to several physiological sensory and motor subsystems that contribute to balance adjustment and dynamic postural control, may help to identify those at risk of adverse health, including dementia [46,47]. Cesari et al [44] found that the FTSS test, as a subtest of the Short Physical Performance Battery, was able to strongly predict mortality (hazard ratio, 0.54; P < 0.01) in a similar way to the complete Short Physical Performance Battery score (hazard ratio, 0.64; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Functional brain imagery study findings point to involvement of the premotor, supplementary motor, and parietal cortex in standing balance control, whereas the hippocampus and premotor cortex are the key region for gait control (Janssen et al, 2002; Rosano et al, 2007; Beauchet et al, 2009, 2012, 2016; Spyropoulos et al, 2013; Wittenberg et al, 2017). Subcortical regions have also been identified as key regions for gait control including the cerebellar locomotor region, the mesencephalic locomotor region, and the subthalamic locomotor region (Bohnen et al, 2011). Gait speed is a surrogate measure of gait, which is the medical term used to globally describe the human locomotor movement of walking (Nutt et al, 1993; Beauchet et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This movement is more unstable in terms of biomechanics, when compared to walking at a comfortable steady-state pace without any disturbances (Spyropoulos et al, 2013). It involves an unstable movement from a static and stable position to a quasi static position (Janssen et al, 2002; Whitney et al, 2005; Bohnen et al, 2011; Schofield et al, 2013; Spyropoulos et al, 2013; Lee et al, 2017). Thus, FTSS time is strongly related to several physiological sensory and motor subsystems which contribute to the dynamic postural control, the most important ones identified in older adults being the muscle strength, lower-limb proprioception, vestibular, and vision subsystems (Janssen et al, 2002; Bohnen et al, 2011; Schofield et al, 2013; Spyropoulos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies indicate that the postural stability increases with an increasing degree of visual control, as in biofeedback mechanisms [23]. Likewise, the performing of a dual-task can influence the motor performance [20,24]. Individuals with PD can perform normal movement patterns when they are focused on the movement performance, i.e.…”
Section: Discussionmentioning
confidence: 99%